The importance of leadership and organizational capacity in shaping health workers’ motivational reactions to performance-based financing: a multiple case study in Burkina Faso - Fillol, Amandine; Lohmann, Julia (International journal of health policy and management, 2019)
Background Performance-based financing (PBF) is currently tested in many low- and middle-income countries as a health system strengthening strategy. One of the main mechanisms through which PBF is assumed to effect change is by motivating health workers to improve their service delivery performance. This article aims at a better understanding of such motivational effects of PBF. In particular, the study focused on organizational context factors and health workers’ perceptions thereof as moderators of the motivational effects of PBF, which to date has been little explored. Methods We conducted a multiple case study in 2 district hospitals and 16 primary health facilities across three districts. Health facilities were purposely sampled according to pre-PBF performance levels. Within sampled facilities, 82 clinical skilled healthcare workers were in-depth interviewed one year after the start of the PBF intervention. Data were analyzed using a blended deductive and inductive process, using self-determination theory (SDT) as an analytical framework. Results Results show that the extent to which PBF contributed to positive, sustainable forms of motivation depended on the “ground upon which PBF fell,” beyond health workers’ individual personalities and disposition. In particular, health workers described three aspects of the organizational context in which PBF was implemented: the extent to which existing hierarchies fostered as opposed to hindered participation and transparency; managers’ handling of the increased performance feedback inherent in PBF; and facility’s pre-PBF levels in regards to infrastructure, equipment, and human resources. Conclusion Our results underline the importance of leadership styles and pre-implementation performance levels in shaping health workers’ motivational reactions to PBF. Ancillary interventions aimed at fostering participatory as opposed to directional leadership or start-up support to low-performing health facilities will likely boost PBF effects in regards to the development of valuable motivational capacities.
ePublished: 26 January 2019
Gesehen am 16.04.2019